Barriers in Access to Dental Services Hindering the Treatment of People with Disabilities: A Systematic Review - Saulo V. da Rosa; Samuel J. Moysés; Laís C. Theis; Renata C. Soares; Simone T. Moysés; Renata I. Werneck; Juliana S. Rocha (Hindawi Limited, 2020)
Background. People with disabilities tend to have greater oral health problems compared to those without disabilities. This may be due to barriers they come across in accessing dental services. Objectives. The objective of this systematic review was to provide a critical digest of the scientific literature concerning barriers and facilitators of access to oral health services for people with disabilities. Methods. The electronic databases PubMed, Scopus, Web of Science, Latin American and Caribbean Health Sciences Literature (LILACS), and Brazilian Library of Dentistry (BBO) were searched using keywords relevant to the subject. The search was not restricted to specific languages or years of publication; all relevant studies were translated and reviewed. Results. Sixteen studies including 14 articles, a doctoral thesis, and a monograph were selected, and their quality was analysed using the Downs and Black assessment tool. Barriers to dental services were divided into physical or nonphysical based on the dentist's perspective, as per the perception of parents/guardians or by the persons with disabilities. The barriers that emerged included the dentist's lack of preparation to assist people with disabilities, structural problems of access to dental offices, communication difficulties, and lack of awareness regarding the need for dental treatment for the disabled person. Conclusion. It is concluded that people with disabilities continue to run into complex physical, behavioural, or multidimensional barriers in accessing dental services. Improved training of dentists for the care of this population is hereby emphasized. The legal framework enabling access to dental care for people with disabilities must also be respected in each country.